2001
DOI: 10.1034/j.1600-0528.2001.290304.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus and oral health: assessment of coronal and root caries

Abstract: Factors associated with presence of coronal and root caries and fillings are discussed. Possible causes and implications for the association between DFS and diabetic nephropathy are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 18 publications
5
51
0
8
Order By: Relevance
“…On the other hand, some of the studies demonstrated lower number of decayed teeth (8,30), while the others reported similar number of decayed teeth in both diabetic and healthy individuals (9,31). However, no relationship between DMFT scores and DM1 was observed in our study which was in accordance with the previous studies suggest that the young diabetic individuals exhibit similar levels of caries with systemically healthy individuals (32,33). This result might be due to the diabetic patients were under control more than 2 years, and as the Lamster et al (34) suggested, carbonhydrate-restricted diet might be the reason of decreased incidence of decayed teeth.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, some of the studies demonstrated lower number of decayed teeth (8,30), while the others reported similar number of decayed teeth in both diabetic and healthy individuals (9,31). However, no relationship between DMFT scores and DM1 was observed in our study which was in accordance with the previous studies suggest that the young diabetic individuals exhibit similar levels of caries with systemically healthy individuals (32,33). This result might be due to the diabetic patients were under control more than 2 years, and as the Lamster et al (34) suggested, carbonhydrate-restricted diet might be the reason of decreased incidence of decayed teeth.…”
Section: Discussionsupporting
confidence: 81%
“…Most recent studies suggest that young people with diabetes exhibit similar levels of caries to systemically healthy individuals (23,24). In this study we found no differences in clinical caries experience between children with diabetes and nondiabetic control children, and the presence of other mucosal lesions was very rare in both groups.…”
Section: Figure 1-distribution Of Periodontal Destruction In the Studmentioning
confidence: 28%
“…[1][2][3][4][5][6] There have been comparatively few studies of the DM adolescent population, in spite of the fact that caries may be more prevalent in this population group. On the other hand, there seems to be no uniform opinion as to whether control of DM or sucrose-free diet of DM patients tends to promote or inhibit the development of dental caries.…”
Section: Introductionmentioning
confidence: 99%